Spirituality in creativity structure as a factor of personality’s psychosocial stability and health optimization [Духовность в структуре креативности как фактор психо-сомостабильности личности и оптимизации ее здоровья] (in Russian) - Иванченко, Андреянна Алексеевна; Іванченко, Андреянна Олексіївна; Ivanchenko, Andreyanna (Кам’янець-Подільський: ПП “Медобори”, 2011)
Spirituality as the most important personal value has a stimulating energy-supplementing effect on the general condition of the personality’s organism, allowing it to reach a more favorable level of life perception. The higher the level of spirituality is, the brighter is the meaningfulness of life. Духовность как важнейшая личностная ценность оказывает стимулирующее энергопополняющее воздействие на общее состояние организма личности, позволяя ей выйти на более благодатный уровень жизневосприятия. Чем выше уровень духовности, тем ярче осмысленность жизни.
Keywords: духовность; жизнесозидающая креативность; лингво-культурологические знания; психо-сомостабильность организма; оптимизация здоровья; обучение итальянскому языку